2021
DOI: 10.1038/s41598-021-98413-x
|View full text |Cite
|
Sign up to set email alerts
|

Bio-oriented synthesis of new sulphadiazine derivatives for urease inhibition and their pharmacokinetic analysis

Abstract: Current research is based on biology-oriented synthesis of sulphadiazine derivatives and determination of their urease inhibitory activity. In this regard, a series of (E)-4-(benzylideneamino)-N-(pyrimidin-2-yl)benzenesulfonamide was synthesized from sulphadiazine and substituted aromatic aldehydes. The structures of synthesized compounds were ascertained by spectroscopic techniques, such as, FTIR, NMR and HRMS analysis, and in-vitro and in-silico investigation were carried out for the inhibition of urease. Ur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
(31 reference statements)
0
8
0
Order By: Relevance
“…11 ) had an aldehyde moiety in its structure, which could explain its high anti‐urease activity 41 . In accordance, Hamad et al reported anti‐urease activity for aldehyde‐incorporated Schiff base derivatives of sulphadiazine 42 …”
Section: Anti‐urease Activitymentioning
confidence: 80%
See 1 more Smart Citation
“…11 ) had an aldehyde moiety in its structure, which could explain its high anti‐urease activity 41 . In accordance, Hamad et al reported anti‐urease activity for aldehyde‐incorporated Schiff base derivatives of sulphadiazine 42 …”
Section: Anti‐urease Activitymentioning
confidence: 80%
“…41 In accordance, Hamad et al reported anti-urease activity for aldehyde-incorporated Schiff base derivatives of sulphadiazine. 42 Saify et al synthesized pyridyl-benzimidazole analogues and reported that the modification of different groups of the phenyl ring of phenacyl could affect the anti-urease activity of the derivatives. Compound 12 that showed the highest anti-urease activity compared with thiourea (IC 50 = 19.42 vs. 21.4 μM, respectively) had an NO 2 group at the R 1 position adjacent to a nitrogen on the pyridine ring, modulating the enzyme's molecular interactions (Figure 3).…”
Section: Anti-urease Activitymentioning
confidence: 99%
“…The magnitude of the calculated dipole moment (D) gives a good indication of the capability of www.nature.com/scientificreports/ the compound to penetrate the biological cell membrane. Generally, the lower the dipole moment, the higher the penetration strength across the phospholipid bilayer 48 . In addition, based on the other calculated molecular descriptors; softness (S), hardness (η), electrophilicity (ω), and electronegativity (χ), the estimated chemical reactivity of the ligands toward metal ions or any neighboring biological receptors is in the order: SB 5 www.nature.com/scientificreports/ SB 2 > SB 3 > SB 1 , where 4 SB 5 is proposed to have the highest softness character (S = 0.300 eV −1 ) and the smallest E, i.e.…”
Section: Molecular Modeling Study Structural Optimization and Reactiv...mentioning
confidence: 99%
“…Effectively short H-bond was observed in most of the docked protein-ligand complexes. As an example, the interaction of SB 1 and SB 4 through O (27) with ARG 115 amino acid and O(9) with ARG 435 amino acid respectively, displayed bond lengths that are less than 3.5 Å 8,48 . Worth mentioning that the negative values of the binding energies (Table 4) indicate spontaneous interaction with the protein.…”
Section: Molecular Modeling Study Structural Optimization and Reactiv...mentioning
confidence: 99%
“…The active site-bearing unit contains approximately 840 amino acids, and the catalytic process relies on the presence of Ni 2+ within the active site. 6 Developing efficient and safe urease inhibitors has received significant attention from the pharmacological research community primarily because ureases play a crucial role in various disease conditions. The ongoing production of ammonia contributes to heightened gastric mucosa permeability, resulting in states such as ulcers, inflammation, lymphoma, and adenocarcinoma.…”
Section: Introductionmentioning
confidence: 99%